2018
DOI: 10.1039/c8ra02978d
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of novel electrochemical sensors based on modification with different polymorphs of MnO2nanoparticles. Application to furosemide analysis in pharmaceutical and urine samples

Abstract: A novel MnO2 nanoparticles/chitosan-modified pencil graphite electrode (MnO2 NPs/CS/PGE) was constructed using two different MnO2 polymorphs (γ-MnO2 and ε-MnO2 nanoparticles).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…For the Fe-promoted systems, the far-infrared region becomes much less structured, as the presence of Fe species seems to bring about more disorder in the crystallographic structure of MnO 2 . FIR spectra of Fe-doped MnO 2 (bluish lines in Figure 2b) suggest the presence of different polymorphs with respect to the previous samples, as already found by XRD analysis [62]; one peak is evident, whereas RAM-MnO 2 definitely causes the appearance of the well-defined band at about 360 cm −1 [60]. As far as it concerns the morphological feature of the examined samples, FEG-SEM microscopy has been carried out in order to visualize the nanoparticles surface texture.…”
Section: Nanoelectrocatalysts Physicochemical Featuressupporting
confidence: 74%
“…For the Fe-promoted systems, the far-infrared region becomes much less structured, as the presence of Fe species seems to bring about more disorder in the crystallographic structure of MnO 2 . FIR spectra of Fe-doped MnO 2 (bluish lines in Figure 2b) suggest the presence of different polymorphs with respect to the previous samples, as already found by XRD analysis [62]; one peak is evident, whereas RAM-MnO 2 definitely causes the appearance of the well-defined band at about 360 cm −1 [60]. As far as it concerns the morphological feature of the examined samples, FEG-SEM microscopy has been carried out in order to visualize the nanoparticles surface texture.…”
Section: Nanoelectrocatalysts Physicochemical Featuressupporting
confidence: 74%
“…Furosemide is the most common drug detected in athlete samples and its occurrence has increased over the years . Only a few studies on the electrochemical determination of furosemide have been reported, where most of them are lacking a quantification range , and are using complex electrode modifications. , This motivated us to study this diuretic drug on the proposed μ-ES. The sensitive detection of furosemide was performed using the SWV technique in 0.1 M phosphate buffer of pH 2.2.…”
Section: Resultsmentioning
confidence: 99%
“…Here, the separation of the peaks for the cathodic and anodic peaks for the two types of MnO 2 /chitosan-modified PGE was only slightly higher than the theoretical value (∆E p = 0.059) signifying the redox couple reversibility of these electrodes, while others demonstrate quasi-reversible behavior at higher values of ∆E p . The chitosan acts to bind the MnO 2 NPs on the electrode surface leading to an increase in peak current because of the electrocatalytic synergy between them [97]. World Journal of Nano Science and Engineering Also, Yang et al gave the CV plot of GPNs/GCE using 5 mM [Fe(CN) 6] +4 in PBS with 0.1 mol/L KCl.…”
Section: Logmentioning
confidence: 99%